1995
DOI: 10.2136/sssaj1995.03615995005900020014x
|View full text |Cite
|
Sign up to set email alerts
|

Near‐Infrared Analysis as a Rapid Method to Simultaneously Evaluate Several Soil Properties

Abstract: The near infrared analysis (NIRA) approach was studied to examine its capability for predicting spectral feature soil properties from the reflectance curves in the near infrared (NIR) region (1-2.5 um) of arid and semiarid soils. High-resolution diffuse reflectance spectra (3113 spectral points) in the NIR region were recorded for 91 soil samples from Israel. Six soil properties (clay content, specific surface area, cation-exchange capacity, hygroscopic moisture, carbonate content, and organic matter content) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
354
4
19

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 710 publications
(395 citation statements)
references
References 0 publications
18
354
4
19
Order By: Relevance
“…Furthermore, this method has been adjusted to analyze the spectrally active properties of sediment and soil samples. For example, many studies have shown that, under laboratory conditions, some soil constituents which have spectral features, such as Fe 2 O 3 (Ji et al 2002), carbonates (Ben-Dor & Banin 1990), organic matter (Dalal & Henry 1986;Reeves et al 2002), and clay (Ben-Dor & Banin 1995;Kooistra et al 2003), can be accurately determined by reflectance spectroscopy. Moreover, recent studies have shown that via the inter-correlation between spectrally featureless constituents and constituents with spectral features, even featureless soil constituents can be predicted by soil reflectance spectra.…”
mentioning
confidence: 99%
“…Furthermore, this method has been adjusted to analyze the spectrally active properties of sediment and soil samples. For example, many studies have shown that, under laboratory conditions, some soil constituents which have spectral features, such as Fe 2 O 3 (Ji et al 2002), carbonates (Ben-Dor & Banin 1990), organic matter (Dalal & Henry 1986;Reeves et al 2002), and clay (Ben-Dor & Banin 1995;Kooistra et al 2003), can be accurately determined by reflectance spectroscopy. Moreover, recent studies have shown that via the inter-correlation between spectrally featureless constituents and constituents with spectral features, even featureless soil constituents can be predicted by soil reflectance spectra.…”
mentioning
confidence: 99%
“…As most instruments are at present only calibrated to fractions of clay, silt and sand, their application in the determination of M50 needs to be developed. Possibly the combination of specific surface area (Ben-Dor and Banin, 1995) and fractions of fine and course sand (Viscarra Rossel et al, 2007, e.g. ) can give an indication.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…The mean raw and first derivative spectra (Figure 2a and b) show strong water and OH -absorption in the NIR near 1400 and 1900 nm (Ben-Dor and Banin, 1995;Clark, 1999). Figure 2b shows characteristic carbonate band with an absorption peak of calcite at 2335 nm as a result of the vibrational combinations and overtones of the CO 3 .…”
Section: Model Performance Evaluationmentioning
confidence: 99%